Patterns of colonic dismotility and visceral hypersensitivity at various clinical variants of irritable bowel syndrome - Ekaterina A. Bubnova; O. Yu. Fomenko; I. L. Khalif; V. V. Pavlenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate motor function disorders of the large intestine and visceral hypersensitivity (VHS) role at various clinical variants of irritable bowel syndrome (IBS). Material and methods. Overall 120 IBS patients were studied. The age of patients varied from 18 to 52 years (mean 34±11,4 years). The diagnosis is verified by modern instrumental and laboratory diagnostic methods (colonoscopy with biopsy, abdominal ultrasonography etc.), and complied to Rome-III criteria. According to specified criteria, all patients were divided into groups according to prevailing symptoms. Twenty-four patients had constipation predominant IBS, 68 had diarrhea predominant variant of IBS, 28 had unclassified IBS variant. All patients underwent investigation of the background and stimulated colonic motility. The motor function of the colon was studied by solid-state catheter manometry method. The balloon-dilatation test was applied to studying of VHS. Results. Investigation of the large intestinal contractility has revealed that 118 of 120 patients had various disorders of colonic motor function. Several patterns of motor activity were determined according to the frequency of contractions: hypokinetic, hypokinetic with segmental contractions, proximal to distal regions contraction discoordination, normokinetic and hyperkinetic. Comparative analysis has revealed that in all patient groups hypokinetic type of motor activity prevails (57%) that indicates decrease of background motility of sigmoid, colon and rectum at IBS. Stimulated motility examination revealed also electric activity disorders of the colon as well. Sixty-five patients underwent balloon and dilatation test: in 40 of them (62%) signs of VHS of were found. Conclusions. Basal electrophysiologic signs of motor and evacuatory function disorders at different IBS variants were not revealed. Nevertheless causative relationship between large intestinal motility changes and disease symptoms is possible. Signs of VHS are found in the most of patients that proves an important role of this factor in the origin of IBS symptoms, especially - in constipation predominant variant.